Array-Comparative Genomic Hybridization Analysis in Fetuses with Major Congenital Malformations Reveals that 24% of Cases Have Pathogenic Deletions/Duplications - Di Gregorio, Eleonora; Gai, Giorgia; Botta, Giovanni; Calcia, Alessandro; Pappi, Patrizia; Talarico, Flavia; Savin, Elisa; Ribotta, Marisa; Zonta, Andrea; Mancini, Cecilia; Giorgio, Elisa; Cavalieri, Simona; et al. (Cytogenetic and genome research, 2015)
Karyotyping and aCGH are routinely used to identify genetic determinants of major congenital malformations (MCMs) in fetal deaths or terminations of pregnancy after prenatal diagnosis. Pathogenic rearrangements are found with a variable rate of 9-39% for aCGH. We collected 33 fetuses, 9 with a single MCM and 24 with MCMs involving 2-4 organ systems. aCGH revealed copy number variants in 14 out of 33 cases (42%). Eight were classified as pathogenic which account for a detection rate of 24% (8/33) considering fetuses with 1 or more MCMs and 33% (8/24) taking into account fetuses with multiple malformations only. Three of the pathogenic variants were known microdeletion syndromes (22q11.21 deletion, central chromosome 22q11.21 deletion, and TAR syndrome) and 5 were large rearrangements, adding up to >11 Mb per subject and comprising strong phenotype-related genes. One of those was a de novo complex rearrangement, and the remaining 4 duplications and 2 deletions were 130-900 kb in size, containing 1-7 genes, and were classified as variants of unknown clinical significance. Our study confirms aCGH as a powerful technique to ascertain the genetic etiology of fetal major congenital malformations.